If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 2 = x + 14 Reorder the terms: 2 + 7x = x + 14 Reorder the terms: 2 + 7x = 14 + x Solving 2 + 7x = 14 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2 + 7x + -1x = 14 + x + -1x Combine like terms: 7x + -1x = 6x 2 + 6x = 14 + x + -1x Combine like terms: x + -1x = 0 2 + 6x = 14 + 0 2 + 6x = 14 Add '-2' to each side of the equation. 2 + -2 + 6x = 14 + -2 Combine like terms: 2 + -2 = 0 0 + 6x = 14 + -2 6x = 14 + -2 Combine like terms: 14 + -2 = 12 6x = 12 Divide each side by '6'. x = 2 Simplifying x = 2
| 2+3[1+2(4+1)]= | | 6(-y+4)-3(2y-3)=-y+5+5y | | 5p-26=18p | | (c+4)3-6c=2(4-2c) | | 7x+5=-51 | | Hyits=a | | 6m=60 | | 24-2[5-(3*1)]= | | 3=5+3t | | 2x-8=12+3x | | 4x+18-6x+38= | | 0=2t^2-13t+21 | | k+5=4k-10 | | -2x+4=-14 | | (5x^2-7x+7)*(6x+9)=0 | | Y+5=4y-10 | | 7+2s-6=6s+8-3s | | 9x^2-34x-8=0 | | 13t-48=2+14t | | 5-2x=-5 | | 3z+15=27 | | 16x^2-320=88x | | 4x-8=12+3x | | 4x^2-2x-9=7x+8 | | 2(4x-3)-=4+2x | | 3z+17=27 | | 8a=3a+35 | | 6y-7=-2y+13 | | x(x+2)=168 | | 4x^2+47x+78=0 | | 15=b-5 | | 3+5n=16 |